Middle Castes Against Hill High Caste Political Domination in Nepal: Can Indian Experience Be A Lesson? - Basnet, Chudamani (Dhaulagiri Journal of Sociology and Anthropology, 2021)
This study examines the problems and prospects of middle caste politics in Nepal based on similar political developments in north India. It investigates the processes of middle caste and class formation in the two countries and goes on to examine demography and upper-caste political strategies. Taking the Federal Socialist Forum Nepal (FSFN) and its trajectory as an example of middle caste political formation, it shows that the middle castes are at a disadvantage in Nepal than their brethren have been in north India. FSFN’s new merger with two political parties recently further shows the difficulty of mobilizing a middle caste political force and mounting a sustained challenge against the political domination of the hill upper castes. This paper also analyzes emerging caste relations in contemporary Nepal.